Linking commitment, compensation, and job satisfaction to employee performance: An empirical study - Razita Nur Sabrina; Gatot Prabantoro (Jurnal Riset Manajemen dan Bisnis, 2025)
This study examines the effects of commitment, compensation, and job satisfaction on employee performance at PT BKI's SBU Marine section, using a quantitative design with a census sample of 80 employees. Data were collected via a structured questionnaire on Google Forms, employing Likert-type scales. Analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. Results show that commitment and job satisfaction significantly positively influence employee performance, while compensation does not have a direct effect. This indicates that enhancing commitment and job satisfaction is more crucial for performance than increasing compensation. The study contributes to the human resource management literature by demonstrating the varying impacts of these factors within a specialized unit. However, it has limitations, including a cross-sectional design and a focus on a single organization. Future research could investigate mediating mechanisms and broaden the sample across multiple organizations.